Kondisi Terumbu Karang di Kepulauan Rajaampat, Kabupaten Sorong - Nurul Dhewani Mirah Sjafrie; Giyanto Giyanto (Universitas Gadjah Mada, 2007)
The study of coral reefs in Rajaampat archipelago, district of Sorong, was carried out in September-October 2001, located at Boni Islands, Ayu Islands and Batang Pele Islands. The aims of this study were to know the percentage of live coral cover, coral diversity and species numbers of coral reefs in this area. Observations on coral reefs were conducted by applying the Rapid Reef Resource Inventory (RRI) and Line Intercept Transect (LIT). Results of Rapid Reef Resources Inventory (RRI) technique showed that the averages of live coral cover on the reef top and reef edge were 6.14 and 15.39% in Boni island (East Waigeo); 6.28 and 24.67% in Ayu island; 25.36 and 23.81% in Batang Pele Islands, respectively. Result of Line Intercept Transect (LIT) technique showed that the percentages of live coral cover were 35.02% in Boni Island, 51.07% in Ayu Island, and 40.86% in Batang Pele Islands. The value of evenness indexs were 0.872-0.934 in Batang Pele Islands; 0.758-0.861 in Ayu Islands; 0.805 in Boni Islands. The total number of species in three sites was 293 species, with the total numbers of spesies in each station were 153 species in Boni islands, 277 species in Ayu islands, and 205 species in Batang Pele Islands. The condition of coral reef at Ayu islands was categorized as good condition, while both of Batang Pele Islands and Boni Islands were categorized as moderate condition.